TUHFAH AL-MURSALAH: STUDI TERHADAP PEMIKIRAN MARTABAT TUJUH AL-BURHANPURY (Al'Adalah, 2004)
In classical Malay literature, al-Burhanpuri was a figure of sufi that have roled significantly in transmitting and developing Islam. Reinterpretation of doctrin of Wihdatul Wujud with seven stages (martabat tujuh) have given smart solution in understanding the matters of wujudiyah. The book of Tuhfah al-Mursalah ila ruh al-Nabiyy have become the most important reference to whom want to understand clearly doctrin of wahdatul wujud in sunni-oriented view.